Growth hormone, prolactin, and corticosteroid responses to insulin hypoglycaemia in alcoholics. Issue 6115 (25th March 1978) - Chalmers, R J; Bennie, E H; Johnson, R H; Masterton, G
Abstract : Plasma growth hormone (GH), prolactin, and corticosteroid responses to insulin-induced hypoglycaemia were studied in 24 men with progressive alcoholism who had been abstinent for two to seven days. Ten normal healthy subjects (five men, five women) served as controls for comparing GH and prolactin responses, while cortisol responses were studied in a further six male controls. Blood samples were taken at intervals after an injection of soluble insulin (0·1 U/kg body weight). All patients developed adequate hypoglycaemia (blood glucose <2·2 mmol/l (<39·6 mg/100 ml)) and nine had impaired GH responses (peak concentration <10 mU/1). Prolactin concentrations fell or remained unchanged in nine patients, eight of whom also had impaired GH responses. In seven patients corticosteroid concentrations decreased from basal concentrations, and six of these patients had impaired GH responses. All three hormone responses were impaired in several patients, and significant correlations were found between the GH and prolactin responses at 45 and 60 minutes. GH response was not correlated with age, duration of drinking, duration of alcoholism, or admitted alcohol intake. GH responses were significantly lower in patients who had the most severe withdrawal symptoms. Our observations of impaired stress responses in some recently abstinent alcoholics may have important implications for the management of alcohol withdrawal syndrome.